The rise of bronze in Central Asia: new evidence for the origin of Bronze Age tin and copper from multi-analytical research - Berger, Daniel; Kaniuth, Kai; Boroffka, Nikolaus; Brügmann, Gerhard; Kraus, Steffen; Lutz, Joachim; Teufer, Mike; Wittke, Andreas; Pernicka, Ernst (Frontiers in Earth Science, 2023)
The Bronze Age in Central Asia was dominated by the Andronovo Culture and the Bactria-Margiana Archaeological Complex (BMAC). Both cultural entities produced bronze, however the extent of bronze production and use varied considerably in space and time across their territories. The introduction and spread of bronze metallurgy in the region is commonly associated with the Andronovo Culture, but comparatively little is known about the copper and tin sources that were exploited to make the bronze. To shed light on this aspect, this paper examines 91 bronze artefacts from the Middle Bronze Age (end of the 3rd millennium BCE) and the Late Bronze Age (until ca. 1300 BCE) recovered from twenty sites of Andronovo and the BMAC through a combined evaluation of chemical and isotopic analyses. Trace element patterns and isotopic compositions of lead, tin, and copper are determined for all objects complemented by tin isotope analysis of Central Asian tin ores. The data shows a clear separation of two source areas in the Middle Bronze Age: the BMAC obtained copper from polymetallic (tin-bearing) deposits in Iran (Deh Hosein, Nakhlak/Bagh Gorogh) and possibly Afghanistan, while the Andronovo Culture mainly used copper from the Tian Shan Mountains. With the transition to the Late Bronze Age II (after 1750 BCE), a change in the material basis can be recognised, in which the BMAC increasingly relied on metal deposits from the Andronovo territory. The most important result in this context is the analytical proof of the extraction of copper and tin from the polymetallic copper-tin deposit at Mushiston, Tajikistan. The mine apparently supplied both cultural macro regions with a “natural” bronze, which accounted for about one third of all objects analysed, but there is no indication yet that metal or ores from Mushiston were traded or used within a radius of more than 500 kilometres. Moreover, the artefact data indicates a decline in the exploitation of the mine in the course of the developed LBA, while other copper and tin sources in the Tian Shan and probably the Hindukush (tin) were exploited.